Enhancement of Biodiesel Yield from High FFA Malaysian Rubber Seed Oil with Sodium Methoxide Treated Limestone - Muhammad, Shahid Ali Wafa; Jolius, Gimbun; Cheng, C. K.; Said, N. (Malaysian Technical Universities Network (MTUN), 2013)
This paper presents the potential of high free fatty acid (FFA) Malaysian rubber seed oil (MRSO) as feedstock for biodiesel production. Precalcinated limestone known as clinker was activated using either methanol or sodium methoxide and transesterification was performed under reflux at constant stirring. Mineral composition of the catalyst was analysed using x-ray fluorescence (XRF) with in build x-ray diffraction (XRD) indicates about 66% of CaO content. The rubber seed oil was obtained using both microwave and soxhlet extraction using hexane as solvent. FFA content and fatty acid methyl ester content were determined using gas chromatography mass spectrometry (GC-MS). The methanol activated limestone based catalyst derived from cement clinker showed an efficient conversion (up to 96.7%) of high FFA rubber seed oil to biodiesel, and the biodiesel yield was 75%. The yield of biodiesel improved significantly (up to 88%) when sodium methoxide loaded clinker was used. The results suggest that the sodium methoxide activated catalyst employed in this work was less likely to be negatively affected by moisture and free fatty acids as compared to the methanol activated catalyst. The biodiesel produced in this work is within the limits of specification described by ASTM D6751.